Hambatan Serta Dampak Pelaksanaan Profil Pelajar Pancasila Dimensi Bernalar Kritis Dalam Proses Pembelajaran Sejarah Di Kelas X SMA Negeri 1 Banjarmasin - Anggelika Permata Sari; Rochgiyanti; Heri Susanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The critical reasoning dimension of students in history learning is quite low, causing a lack of ability in solving problems, lack of curiosity, and learning that is still monotonous makes students lazy and bored in the learning process. To overcome this problem, one of them is done through the Pancasila student profile, by applying 6 dimensions. The purpose of this study was to analyze the obstacles and impacts of the Pancasila student profile of the critical reasoning dimension on the history learning process in class X of SMA Negeri 1 Banjarmasin. This study used a qualitative method. The subjects of the study were 35 students of class X-5 of SMA Negeri 1 Banjarmasin using a questionnaire and 5 students in-depth interviews, 1 history subject teacher, and a curriculum representative. Data obtained through observation of teacher activities, student activities, critical reasoning skills and student motivation in the learning process. Data analysis techniques in this study were the implementation of learning and evaluation. In the application of the Pancasila student profile, the critical reasoning dimension has obstacles, namely internal and instrumental factors, as well as negative and positive impacts. The conclusion of the study was several obstacles and impacts that occurred in the learning process, but could still be overcome by schools and teachers. Suggestions for school principals, teachers, and other researchers are that this research can be used as an option in implementing the Pancasila student profile in the critical reasoning dimension in the history learning process.